The health burden of chronic diseases in the United States attributable to air particulate matter - Manan Raina; Jieji Hu; Raghav Shah; Max Gilliland; Sanjay Rajagopalan (Clinical Medicine)
Background: There is an established link between air pollution and chronic disease. In this study, we measure the impact and health burden of fine particulate matter (PM2.5) in chronic disease in the United States (USA), specifically type 2 diabetes mellitus (T2DM), chronic obstructive pulmonary disease (COPD), ischaemic heart disease (IHD) and stroke. Methods: Data on the global burden of chronic disease attributable to air pollution were obtained from Global Burden of Diseases (GBD) 2021 study. The number of deaths and disability-adjusted life years (DALYs) attributable to air pollution from 1990 to 2021 were extracted and analysed by different US locations and years. Results: The death rates due to chronic diseases attributable to PM2.5 in the USA have decreased significantly. In 2021, death rates were lowest for T2DM (1.307), followed by stroke (2.004), COPD (2.119) and IHD (5.865). Between 1990 and 2021, death rates declined by 36% for T2DM, 30% for COPD, 70% for IHD and 61% for stroke. DALY rates in 2021 were lowest for stroke (52.389), followed by COPD (54.147), T2DM (73.32) and IHD (119.471), with reductions of 16.4%, 39.6%, 70.3% and 58.9%, respectively, since 1990. High-sociodemographic index (SDI; a measure of social and economic development) states saw greater improvements, with average annual percentage change (AAPCs) of −5.2% for IHD and −2.68% for COPD, compared to −4.4% and −1.35% in low-SDI states. Higher-income states also showed faster declines, such as an AAPC of COPD death rates of −2.51% versus −1.21% in low-income states. Discussion: The results highlight a decreasing trend in death rates and DALYs and identify varying locations that remain at high risk of health burden from PM2.5-associated chronic disease. There is a continued need for addressing air pollution control and policy revisions targeted to patient subpopulations in the USA where the burden of PM2.5 can still be detrimental.